Down-regulation of cyclin D2 in amyloid β toxicity, inflammation, and Alzheimer’s disease - Grzegorz A. Czapski (Public Library of Science (PLoS), 2021)
In the current study, we analyzed the effects of the systemic inflammatory response (SIR) and amyloid β (Aβ) peptide on the expression of genes encoding cyclins and cyclin-dependent kinase (Cdk) in: (i) PC12 cells overexpressing human beta amyloid precursor protein (βAPP), wild-type (APPwt-PC12), or carrying the Swedish mutantion (APPsw-PC12); (ii) the murine hippocampus during SIR; and (iii) Alzheimer’s disease (AD) brain. In APPwt-PC12 expression of cyclin D2 (cD2) was exclusively reduced, and in APPsw-PC12 cyclins cD2 and also cA1 were down-regulated, but cA2, cB1, cB2, and cE1 were up-regulated. In the SIR cD2, cB2, cE1 were found to be significantly down-regulated and cD3, Cdk5, and Cdk7 were significantly up-regulated. Cyclin cD2 was also found to be down-regulated in AD neocortex and hippocampus. Our novel data indicate that Aβ peptide and inflammation both significantly decreased the expression of cD2, suggesting that Aβ peptides may also contribute to downregulation of cD2 in AD brain.